Pengaruh Badan Usaha Miliki Desa terhadap Kinerja Keuangan Pemerintah Daerah Istimewa Yogyakarta - Agnisa Widayanti; Ratna Candrasari (Inspirasi Nusantara, 2021)
This study aims to determine how financial performance of the regional government in Yogyakarta before the BUMDes 2010-2013 and after the BUMDes 2014-2018. This study uses a descriptive method with a quantitative approach to analyze the financial performance of regional government in Yogyakarta before BUMDes 2010-2013 and after BUMDes 2014-2018 using Independence Ratio, Efficiency Ratio, Decentralization Ratio, and Capital Expenditure Harmony Ratio. This study using secondary data which get from Regional Revenues and Expenditures Yogyakarta 2010-2018. The result of this study based on Independence Ratio is the independence of financial performance before BUMDes was very low and independence of financial performance after BUMDes still low but its increase than before, Efficiency Ratio show financial performance before BUMDes was efficient and financial performance after BUMDes not efficient, based on Decentralization Ratio financial performance before BUMDes was very low and financial performance after BUMDes still low but its increase than before, capital Expenditure Harmony Ratio shows that capital expenditure ratio before BUMDes and after BUMDes still proper.